PRANA DAN GAYA HIDUP : UPAYA MENINGKATKAN ENERGI VITAL TUBUH - Rahmawati, Putu Reny (Institut Hindu Dharma Negeri Denpasar, 2019)
Pranayama is breath control in yoga. Pranayama controls prana (vital energy) in the body, with the controlled and controlled withdrawal and exhalation resulting in increased vital energy so that it can influence the mind more calmly and the body more healthy. By doing the practice of Pranayama and making it a lifestyle in the present or the modern era, it can make a person more healthy and have a much better mind. Some pranayama practices that can be done are: Suryabedha Pranayama, Sitali Pranayama, Sitkari Pranayama, Ujayi Pranayama, Bashrika Pranayama, Kapalabhati Pranayama and many more Pranayama with different benefits according to the needs of yoga practitioners and remain in increasing vital energy in the body